AN ATTEMPT TO DETERMINE THE FUNCTIONAL AREA OF WARSAW WITH THE USE OF THE MEASURE OF RELATIVE DEVELOPMENT LEVEL AND HELLWIG&APOS;S MEASURE - Chrzanowska, Mariola; Drejerska, Nina; Pomianek, Iwona (Acta Scientiarum Polonorum. Oeconomia, 2013)
Mazovian Voivodeship is an area where socio-economic situation is significantly diverse. It is a real challenge for regional development policy which in Poland aims at increasing competitiveness and achieving cohesion by 2020. The use of selected taxonomic measures to compare the development level of selected communes in Mazovia allowed to determine whether the regional policy so far has led to socio-economic growth of all or just some of the investigated communes. Those urban-rural and rural communes of the highest development level in the Mazovia region seem to create a quite coherent area around Warsaw; it was proved by the results of statistical analysis with the use of the relative development level and Hellwig's measure for the years 2002 and 2009.